The Industrialisation of Soviet Russia 3: The Soviet Economy in Turmoil 1929-1930 - Davies, R. W. author. aut Link
XX, 601 p.
Keywords: In 1929-30, the 'spinal year' of the first five-year plan, a vast investment programme began the transformation of the Soviet Union from a peasant country into a great industrial power. This book, the third part of The Industrialisation of Soviet Russia, re-examines the breakdown of the mixed economy. In those days of heroism and enthusiasm, hunger and repression, crucial Soviet economic and political institutions were established, and are only now being effectively challenged by Gorbachev's revolution. While complementing the previous two volumes of this author's work, the book is designed to be read independently. It sheds new light on a dramatic moment in Soviet history and in the formation of the Soviet system.